Pelayanan kefarmasian dan edukasi pada peserta khitanan massal di Desa Tanjung Kidul - Fahmi Dimas Abdul Azis; Rokayah; Endah S; Royhan Hanin S; Rio Renaldi H (P3HKI - Universitas Muhammadiyah Parepare, 2022)
The Mass Circumcision event took place on June 13, 2022, at Tanjung Kidul Village, Paiton District, Probolinggo Regency, located in the East Java Province. The community in the village of Tanjung Kidul actively participates as partners in the circumcision activities. Circumcision, referred to as